Pengaruh Tata Ruang Kantor terhadap Semangat Kerja Pegawai - Mufidah Nuraini; Patni Ninghardjanti; Hery Sawiji (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2023)
This study aims to determine the influence of office layout on employee morale in BKPSDM Karanganyar Regency. This research is quantitative research. The population in this study were all 37 employees of BKPSDM Karanganyar Regency. Sampling in this study used a saturated sampling technique. Data collection was carried out by distributing questionnaires. The technique of analyzing data used simple linear regression analysis by using SPSS 25.0 program. The results showed that the office layout has positive and significant influence on the work spirit (tcount 5,201 >ttable 2,030). The result of this study indicate that office layout contributed as much as 43,6% on work spirit’s employee while 56,4% is influenced by other factors